Revisiting preferences for communication styles in computer-mediated communication: a study amongst UK and Arab samples - Elfadl, Asma; Alshakhsi, Sameha; Ali, Raian; Yankouskaya, Ala (Telematics and Informatics Reports, 2025)
As the transition toward online communication continues globally, the way people interact across cultures is also evolving. Much of the research on communication styles has focused on face-to-face communication, while less attention has been given to how such styles adapt in digital spaces, especially across different cultural groups. This study addresses that gap by examining cross-cultural differences in online communication styles between the UK and Arab Gulf Cooperation Council (GCC) countries. Supported by scenarios and explanations, we surveyed 599 adults (272 from the UK and 327 from Arab GCC countries), assessing their preferences for well-defined communication styles (Direct vs. Indirect, Ordered vs. Unordered, Being-centred vs. Doing-centred, Literate vs. Oral) and their comfort levels with each. Our results indicate that online communication preferences in these cultures are becoming more aligned, as shown by both Arab and UK participants expressing greater preference of direct communication, thus challenging traditional cultural norms. We also observed a trend toward a being-centred communication style in the UK sample and differences in comfort levels with structured communication (ordered or linear) across the cultures. Interestingly, in contrast to face-to-face communication, no differences were found between the cultures in their preferences for literate versus oral communication styles. These findings suggest that digital environments may promote more flexible and adaptive communication, adding new evidence to the Uncertainty Avoidance and Communication Accommodation theories.